CCL18 differentiates dendritic cells in tolerogenic cells able to prime regulatory T cells in healthy subjects - Azzaoui, Imane; Yahia, Saliha Ait; Chang, Ying; Vorng, Han; Morales, Olivier; Fan, Ying; Delhem, Nadira; Ple, Coline; Tonnel, André-Bernard; Wallaert, Benoit; Tsicopoulos, Anne (Blood, 2011)
The aim of this study was to evaluate the nonchemotactic function of CCL18 on human dendritic cells (DCs). In different protocols of DC differentiation, CCL18 was highly produced, suggesting that it may constitute a mandatory mediator of the differentiation process. Differentiation of monocytes from healthy subjects in the presence of granulocyte-macrophage colony-stimulating factor and CCL18 led to the development of DCs with a semimature phenotype, with intermediate levels of costimulatory and MHC class II molecules, increased CCR7 expression, which induced, in coculture with allogenic naive T cells, an increase in IL-10 production. The generated T cells were able to suppress the proliferation of effector CD4+CD25− cells, through a cytokine-dependent mechanism, and exhibited characteristics of type 1 T regulatory cells. The generation of tolerogenic DCs by CCL18 was dependent on the production of indoleamine 2,3-dioxigenase through an interleukin-10-mediated mechanism. Surprisingly, when DCs originated from allergic patients, the tolerogenic effect of CCL18 was lost in relation with a decreased binding of CCL18 to its putative receptor. This study is the first to define a chemokine able to generate tolerogenic DCs. However, this function was absent in allergic donors and may participate to the decreased tolerance observed in allergic diseases.